Jargões no funcionamento multimodal da linguagem de crianças autistas em interação com um parceiro enunciativo. - Berg, William (2024)
Jargon is a vocal production present in the linguistic trajectory of (a)typical children that is often unnoticed by interlocutors. This is because this jargonized vocal production resembles recognizable words in the language in terms of consonant-vocal structure, but, semantically, it has no apparent meaning whether analyzed in isolation, in addition to being used as a clue for diagnosing people with atypical conditions, as in the case of autistic children. However, moving away from this conception, we perceive jargon as a language possibility that can be (re)signified by the enunciative partner, just as occurs with the other prosodic-vocal elements (babbling, holophrase, enunciation block) of the oral axis. In the light of multimodality, jargon is given semiotic prominence insofar as the multimodal perspective allows for a multisemiotic analysis, ie in addition to jargon (vocal production) the semioses: gesture, gaze, facial expression etc. co-exist in the same instance, thus forming a single matrix of meaning a thesis defended by (inter)national researchers such as Kendon (1982, 2000, 2016), McNeill (1985, 1992, 2000), Butcher, Goldin-Meadow (2000), Fonte, Barros, Cavalcante e Soares (2014), Fonte and Cavalcante (2016), Cavalcante (2018). In view of this, this research aims to investigate the jargon produced by autistic children in the multimodal functioning of language through the effect produced on the interactive partner. More specifically, to identify and describe the multimodal elements integrated into the jargon of autistic children in interactive situations; to analyze the intonational contours of the jargon of these children associated with multimodal elements, especially the gestural modality, in an interactive scene; to verify the role of the multimodal elements associated with the jargon of autistic children and the effect produced on their interactive partner. To do this, we used videos of three autistic children in a variety of interactive contexts, which were stored in the database of the Language Practices Laboratory of the Graduate Program in Language Sciences (PPGCL) at the Catholic University of Pernambuco. The interactive scenes analyzed took place in the Autism Study and Reception Group (GEAUT). We used ELAN software to transcribe vocal production, gestures and gaze, while PRAAT helped with the acoustic analysis of jargon. In our analysis, we identified that the autistic children Jorge, Bruno and Henrique produced different semioses (gestures, facial expression and gaze) concomitantly with the jargonized vocal productions, provoking effects and reactions in the interlocutors, such as strangeness and excitement. With this, we realize, from a holistic analysis of jargon, that autistic children are able to enunciate their thoughts and ideas just like a typical child. All that is needed is for the interlocutor to understand that the nature of how language works is multimodal, in order to transpose jargon to a meaningful level. Furthermore, this research has led to promising discussions about jargon in autistic children and for the science of language, since it is a little-explored topic.